Maximal sprints within the warm-up does not affect pacing or performance in a 10 km cycle time trial - Veen, J.; Corbett, M.; Renfree, A. (Journal of Human Sport & Exercise, 2020)
This study investigated the effects of the inclusion of a post activation potentiation (PAP) specific warm-up (WU) consisting of all-out sprints on 10-kilometre cycling time trial (10 km-TT) pacing and performance. Following familiarization, thirteen well-trained male participants performed two 10 km cycle laboratory time trials following warm-ups that included either four 8 seconds (s) maximal sprints, or a matched total work performed at a constant exercise intensity. Power output (PO), heart rate (HR), and ratings of perceived exertion (RPE) were measured throughout and blood lactate (BLa) 3 minutes post exercise. There were no significant differences in total performance time, PO in any 2 km segment, RPE, or post-exercise BLa between conditions. Some significant differences (p < .05) were observed in heart rate and cadence between 2 km segments. Addition of four all-out sprints to the WU did not improve 10 km time trial performance or alter pacing strategy displayed. This suggests that maximal sprinting in a warming up might not be an effective strategy to improve cycling time trial endurance performance.